Intravenous levetiracetam versus phenobarbital in children with status epilepticus or acute repetitive seizures - Lee, Yun-Jeong (Korean J Pediatr, 2016)
PURPOSE: This study compared the efficacy and tolerability of intravenous (i.v.) phenobarbital (PHB) and i.v. levetiracetam (LEV) in children with status epilepticus (SE) or acute repetitive seizure (ARS). METHODS: The medical records of children (age range, 1 month to 15 years) treated with i.v. PHB or LEV for SE or ARS at our single tertiary center were retrospectively reviewed. Seizure termination was defined as seizure cessation within 30 minutes of infusion completion and no recurrence within 24 hours. Information on the demographic variables, electroencephalography and magnetic resonance imaging findings, previous antiepileptic medications, and adverse events after drug infusion was obtained. RESULTS: The records of 88 patients with SE or ARS (median age, 18 months; 50 treated with PHB and 38 with LEV) were reviewed. The median initial dose of i.v. PHB was 20 mg/kg (range, 10–20 mg/kg) and that of i.v. LEV was 30 mg/kg (range, 20–30 mg/kg). Seizure termination occurred in 57.9% of patients treated with i.v. LEV (22 of 38) and 74.0% treated with i.v. PHB (37 of 50) (P=0.111). The factor associated with seizure termination was the type of event (SE vs. ARS) in each group. Adverse effects were reported in 13.2% of patients treated with i.v. LEV (5 of 38; n=4, aggressive behavior and n=1, vomiting), and 28.0% of patients treated with i.v. PHB (14 of 50). CONCLUSION: Intravenous LEV was efficacious and safe in children with ARS or SE. Further evaluation is needed to determine the most effective and best-tolerated loading dose of i.v. LEV.